A CONSTITUIÇÃO DO ETHOS DISCURSIVO EM GÊNERO ENTREVISTA - Veloso, Simone Ribeiro de Ávila (Intercâmbio, 2010)
This paper intends to analyse the scientific vulgarization discourse through interviews published by Veja´s. It will be considered the concept of ethos by Dominique Maingueneau. The objective is to understand the social representations articulated by the journalist area and by the interview genre.